Presente y futuro del Estado de bienestar el debate europeo - Beck, Ulrich (Siempro Miño y Dávila, 2001)
Colaboradores: LE GRAND, Julian; GLENNERSTER, Howard; ESPING ANDERSEN, Gosta; PAUGAM, Serge; ESTADO BENEFACTOR; CIUDADANO